Heating elements of flexible tape in current mode power supply of complex form - E. V. Ptitsyna; D. V. Ptitsyn; A. B. Kuvaldin (Омский научный вестник)
The paper presents the results of studies of energy and technological parameters of the elements of heating flexible tape at different electrical modes: when powered by alternating current of 50 Hz; constant (rectified) current; current of complex form with a constant component and without it. The purpose of the work is to study the influence of electrical modes on the energy and technological parameters of heaters to develop recommendations for the selection of effective modes of operation of such heaters when powered by a complex form of current to develop automated control systems, involving the use of two control channels: the amplitude of voltage (current) and the frequency spectrum.